MANAJEMEN SELEKSI INDUK DALAM PEMBENIHAN IKAN CUPANG DI SMK NEGERI 1 MEUREUBO ACEH BARAT - Fazril Saputra; Citra Dina Febrina; Dini Islama (Jurnal Marine Kreatif, 2020)
This service aims to provide knowledge to students of SMK Negeri 1 Meureubo, West Aceh about the management of parent selection in betta fish hatchery activities. Betta fish was a type of ornamental fish that was very popular among people from the top and bottom as well as from children to adults. If done seriously, betta fish farming has bright prospects and can increase people's income. Betta fish farming can run with minimal capital but produces promising profits. However, in cultivating betta fish, many cultivators encounter various obstacles, especially for beginners. One of the obstacles encountered in the cultivation of betta fish was the hatchery phase. In this phase, beginners find it difficult to choose hickey sires that were ready to be spawned.To overcome the obstacles of hatching betta fish for novice cultivators, this community service program was carried out. The solution offered by this community service was to provided additional skills to students of SMK Negeri 1 Meureubo Meulaboh, West Aceh to be able to select broodstock for good and correct betta fish breeders in accordance with SNI for ornamental betta fish. The service method was a discussion and direct practice of how to select the correct and correct parent betta fish (Betta sp.). The results obtained from the dedication are that the students of SMK Negeri 1 Meureubo Meulaboh, West Aceh were very enthusiastic about breeding ornamental betta fish (Betta sp.) and hope that this community service program can continue to be implemented to provide assistance to students of SMK Negeri 1 Meureubo Meulaboh, Aceh West.